Analisis Sentimen Game Genshin Impact pada Play Store Menggunakan Naïve Bayes Clasifier - Primandani Arsi; Pungkas Subarkah; Bagus Adhi Kusuma (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2023)
Online games are an entertainment medium that cannot be separated from some groups of people, especially during the co-19 pandemic. The existence of a policy of violence reduces the interaction of people in the world, including in Indonesia, resulting in an increase in online activity, especially playing games. Game is an interesting online gaming platform, where players can still interact socially boldly. Genshin Impact is a mobile game that provides other platforms such as PC, PlayStation and Nintendo Switch. Although some people like this game, others are not satisfied with the game play. Sentiment analysis is also very useful when game developers want to know what users think about the game experience. This research aims to build a model of the classification of reviews on the Genshin Impact game available on the Google Play platform, so that the resulting model can provide recommendations for developers for improvement. The results obtained are reviews on the Google Play Store tend to be positive with an accuracy score of 87%, precision of 67%, memory of 98%, and f1 score of 67%. Evaluation is done by comparing the model that has been obtained in this study with the previous model with the same algorithm.